Fyodor Dostoevsky in 21st-Century Foreign Research - Violetta D. Evallyo (Достоевский и мировая культура: Филологический журнал, 2023)
This article attempts to provide an overview of foreign monographs and collective works that have been published in the 21st century, as well as some significant translations and reprints. This review cannot claim to provide an exhaustive overview of all authors’ approaches, but some conclusions can be drawn from it anyway. Firstly, the identified problems which are in the focus of contemporary researchers differ in many respects from those which were the focus of attention of researchers in previous decades, and this seems to be due to the issues that concern different generations. The focus of scholars’ attention is still on ontological problems, eternally troubling humans – questions of spirituality, good and evil, humanism and the limits of the mankind, however, more and more space is occupied by contemporary issues: intolerance, femininity, trauma, deviancy, cruelty, nihilism. In Dostoevsky’s works, researchers are attracted by the prophetic motifs of the consequences of the loss of spirituality and ethical foundations – and possible ways of redemption.